Work-related Traumatic Fatal Injuries Involving Confined Spaces - Selman, Jason Stuart (Curtin University, 2019)
Many workers die each year from work-related confined space incidents. The rate of confined space fatalities in Australia was found to be comparable to similarly industrialised countries; and an examination of the aetiologies involved found fatalities were approximately equally from both atmospheric hazards and from physical hazards. Up to 17% of fatalities were found to be those undertaking rescue, overwhelmingly from hazardous atmospheres. Strategies to reduce confined space fatalities were developed.